Changing social investment strategies in the EU - Sara Baiocco; Cinzia Alcidi; Francesco Corti; Mattia Di Salvo (European Commission, Joint Research Centre (JRC), 2022)
This article attempts to identify social investment strategies across EU countries and explain their evolution over the period 2004-18, by using cluster analysis on expenditure and coverage variables and qualitative analysis on selected policy areas to contextualize the results. It finds that strategies have diversified over time in a progressively complex way. After the financial crisis, three main social investment strategies emerge in Europe. They do not overlap with canonical welfare state models, nor have a clear-cut geographical connotation. The strategies are distinct because of their different levels of overall expenditure on social investment but, over time, also by their different life-course orientations. Significant variation within the clusters, in terms of both expenditure and design of social investment policies, indicates that fully-fledged strategies have not yet formed in well-defined groups of countries.
Keywords: 330; Sara Baiocco; Cinzia Alcidi; Francesco Corti; Mattia Di Salvo; Social investment; cluster analysis; welfare state